Biohydrogen production from traditional Chinese medicine wastewater in anaerobic packed bed reactor system. Issue 10 (1st February 2021) - Sun, Caiyu; Sheng, Tao; Li, Lixin; Yang, Lisha
Abstract : Three anaerobic bed reactors packed with activated carbon, maifanite and tourmaline were continuously operated for 165 days to generate hydrogen from traditional Chinese medicine wastewater at different loading rates (15.2 to 91.3 g COD L −1 d −1 ). Abstract : Three anaerobic packed bed reactors (APBR) packed with activated carbon, maifanite and tourmaline as support material were continuously operated for 165 days to generate hydrogen from traditional Chinese medicine wastewater at different organic loading rates (OLR) from 15.2 to 91.3 g COD L −1 d −1 by changes of hydraulic retention time (HRT) varying from 24 to 6 h. The best performance with hydrogen production rate (HPR) of 7.92 ± 0.27 mmol L −1 h −1 and hydrogen yield (HY) of 3.50 ± 0.09 mmol g −1 COD was achieved for the reactor with tourmaline at OLR of 60.8 g COD L −1 d −1 (HRT = 6 h), followed by activated carbon and maifanite. The main metabolic products for each reactor were found to be acetate and butyrate in the effluent with pH range of 5.6–6.4 and microbial analysis revealed that the dominant communities in all cultures were C. carboxidivoran and C. butyricum, responsible for acetate and butyrate production respectively.